Feed-grade hempseed as alternative protein source in organic broilers diet: Growth performance, carcass characteristics and meat quality - Francesco Serrapica; Claudia Lambiase; Felicia Masucci; Ada Braghieri; Jose Manuel Lorenzo; Antonio Di Francia (Journal of Agriculture and Food Research)
This study investigated the feasibility of integrating feed-grade hempseed (FG-HS), an emerging by-product of the oil industry, into organic poultry production, focusing on its impact on growth performance, slaughter yield, and quality traits of meat in medium-growing chickens. Soybean expeller cake (SBE) was used for comparison. One hundred and twenty 21-day-old chickens were assigned to three dietary groups, each consisting of two replicates of twenty chickens. Treatments included a control diet containing 30 % SBE and two experimental diets with FG-HS replacing SBE at 50 % (H15) or 100 % (H30). Trial lasted 14 weeks. At the end of the experimental period, birds were sacrificed for carcass evaluation, including welfare-related traits. Rheological, nutritional, and sensory properties of breast meat were also evaluated. Birds fed the H30 diet showed a trend toward lower incidence of footpad dermatitis (P = 0.06), cleaner plumage (P < 0.03), higher final live weight (P < 0.05), and heavier viscera (P < 0.05) compared to the SBE and H15 groups. No effects of diet were found for eviscerated carcass weights, commercial cut yield or meat quality traits such as composition, amino acid profile, water holding capacity, and Warner-Bratzler shear force. Notably, FG-HS inclusion significantly reduced saturated fatty acid levels (P < 0.001 and P < 0.05 for H30 and H15 diets, respectively), while increasing polyunsaturated fatty acids (P < 0.01 and P < 0.05). The H30 diet enhanced overall flavor intensity (P < 0.01) and significantly reduced (P < 0.01) fibrousness, gumminess, and mouth residue. Results suggest that FG-HS can be successfully integrated into broiler diets at inclusion rates up to 30 % without compromising bird growth performance, carcass and meat traits. Moreover, FG-HS at the highest inclusion level shows potential for enhancing breast meat quality in terms of fatty acid profile and sensory characteristics.